Binary Diffusion Coefficients for Mixtures of Ionic Liquids [EMIM][N(CN)(2)), [EMIM][NTf2], and [HMIM][NTf2] with Acetone and Ethanol by Dynamic Light Scattering (DLS) - Rausch, Michael Heinrich; Hopf, Lisa; Heller, Andreas; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2013)
Mutual diffusivities for binary mixtures of the ionic liquids (ILs) [EMIM] [N(CN)(2)] (1-ethyl-3-methylimidazolium dicyanimide), [EMIM] [NTf2] (1-ethyl-3-methylimidazolium bis-(trifluoromethylsulfonyl)imide), and [HMIM] [NTf2] (1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) with acetone and ethanol were studied in dependence on composition in the temperature range from 283.15 to 323.15 K, applying dynamic light scattering (DLS). The influence of experimental parameters on the achievable uncertainties was analyzed to ensure the acquisition of accurate data in adequate measurement times. For all probed systems, increasing binary diffusion coefficients were found for increasing temperatures. The systematic variation of anion and cation of the investigated ILs as well as a comparison with the literature data demonstrates the considerable influence of different ions on the resulting binary diffusion coefficients. Mutual diffusivities were found to be lower for the mixtures with ethanol than for those with acetone, which could be related to the formation of hydrogen bonds between ethanol and the ions. Most of the investigated IL solvent mixtures show increasing binary diffusion coefficients with increasing solvent concentration. For the mixtures of [EMIM][NTf2] with ethanol, however, a minimum of the mutual diffusivities was found in the ethanol mole fraction range from 0.7 to 0.8, which may hint at the vicinity of a critical demixing point. The viscosity of the pure ILs turned out to be no reliable indicator for the mutual diffusivity in mixtures with the same solvent.

Binary Diffusion Coefficients of Glycerol-Water Mixtures for Temperatures from 323 to 448 K by Dynamic Light Scattering - Rausch, Michael Heinrich; Heller, Andreas; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2017)
The binary diffusion coefficients of mixtures consisting of glycerol and water with glycerol mole fractions of 0.299, 0.500, and 0.699 were investigated by dynamic light scattering (DLS) in macroscopic thermodynamic equilibrium over the temperature range 323-448 K. Furthermore, a beam displacement method implemented in the same experimental setup was used to determine the refractive indices of the mixtures required for the evaluation of the DLS measurements. The reported results represent the first temperature-dependent data set for the binary diffusion coefficient of glycerol water mixtures, where increasing diffusion coefficients were found for increasing temperature and decreasing glycerol concentration. The latter finding is consistent with literature data that are restricted to specific temperatures. The present results are in good agreement with the absolute values and concentration-dependent trends of the binary diffusion coefficients for glycerol water mixtures available in the literature.

Binary Diffusion Coefficients of the Liquid Organic Hydrogen Carrier System Dibenzyltoluene/Perhydrodibenzyltoluene - Heller, Andreas; Rausch, Michael Heinrich; Schulz, Peter; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2016)
Liquid organic hydrogen carrier (LOHC) systems constitute a very promising concept for future hydrogen storage and logistics. The concept builds on the conversion of excess renewable energy to hydrogen via electrolysis followed by reversible catalytic hydrogenation/dehydrogenation of a diesel-like organic carrier molecule. For an ideal design of the catalytic process, insight into reaction mechanisms and kinetics but also precise knowledge on mass transport properties are necessary. In the present study, binary diffusion coefficients in selected binary LOHC mixtures with five different compositions of perhydrodibenzyltoluene (H-18-LOHC) and dibenzyltoluene (LOHC) were measured by dynamic light scattering (DLS). The compositions were defined by mixing appropriate amounts of LOHC and H-18-LOHC to realize different hydrogenation degrees of the LOHC. Binary diffusion coefficients were investigated over a temperature range from (264 to 571) K with an absolute uncertainty of (3 to 25) %. Moreover, an empirical equation describing the binary diffusion coefficients of all five mixture compositions over the complete temperature range with a root-mean-square deviation of less than 3 % was established. It was observed that the binary diffusion coefficient is independent of the hydrogenation degree of LOHC at temperatures above 430 K. For lower temperatures, the binary diffusion coefficient increases with decreasing degree of hydrogenation.

Diffusivities of Ternary Mixtures of n-Alkanes with Dissolved Gases by Dynamic Light Scattering - Heller, Andreas; Giraudet, Cédric; Makrodimitri, Zoi A.; Fleys, Matthieu S. H.; Chen, Jiaqi; van der Laan, Gerard P.; Economou, Ioannis G.; Rausch, Michael Heinrich; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2016)
Theoretical approaches suggest that dynamic light scattering (DLS) signals from low-molecular-weight ternary mixtures are governed by fluctuations in temperature as well as two individual contributions from fluctuations in concentration that are related to the eigenvalues of the Fick diffusion matrix. Until now, this could not be proven experimentally in a conclusive way. In the present study, a detailed analysis of DLS signals in ternary mixtures consisting of n-dodecane (n-C12H26) and n-octacosane (n-C28H58) with dissolved hydrogen (H-2), carbon monoxide (CO), or water (H2O) as well as of n-C12H26 or n-C28H58 with dissolved H-2 and CO is given for temperatures up to 523 K and pressures up to 4.1 MPa. Thermal diffusivities of pure n-C12H26 and n-C28H58 as well as thermal and mutual diffusivities of their binary mixtures being the basis for the ternary mixtures with dissolved gas were studied for comparison purposes. For the investigated ternary mixtures, three individual signals could be distinguished in the time-resolved analysis of scattered light intensity by using photon correlation spectroscopy (PCS). For the first time, it could be evidenced that these signals are clearly associated with hydrodynamic modes. In most cases, the fastest mode observable for ternary mixtures is associated with the thermal diffusivity. The two further modes obviously related to the molecular mass transport are observable on different time scales and comparable to the modes associated with the concentration fluctuations in the respective binary mixtures. Comparison of the experimental data with results from molecular dynamics simulations revealed very good agreement.

Model development for the gas-to-liquid process based on molecular simulation and experimental measurements of physical properties - Economou, Ioannis G.; Makrodimitri, Zoi A.; Fröba, Andreas Paul; Koller, Thomas Manfred; Heller, Andreas; Rausch, Michael Heinrich; Fleys, Matthieu S. H.; Bos, A. N. Rene; Unruh, Dominik (Computational Molecular Science and Engineering Forum 2013 - Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)

Mutual and Self-Diffusivities in Binary Mixtures of [EMIM][B(CN)(4)] with Dissolved Gases by Using Dynamic Light Scattering and Molecular Dynamics Simulations - Koller, Thomas Manfred; Heller, Andreas; Rausch, Michael Heinrich; Wasserscheid, Peter; Economou, Ioannis G.; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2015)
Ionic liquids (ILs) are possible working fluids for the separation of carbon dioxide (CO2) from flue gases. For evaluating their performance in such processes, reliable mutual-diffusivity data are required for mixtures of ILs with relevant flue gas components. In the present study, dynamic light scattering (DLS) and molecular dynamics (MD) simulations were used for the investigation of the molecular diffusion in binary mixtures of the IL 1-ethyl-3-methylimidazolium tetracyanoborate ([EMIM][B(CN)(4)]) with the dissolved gases carbon dioxide, nitrogen, carbon monoxide, hydrogen, methane, oxygen, and hydrogen sulfide at temperatures from 298.15 to 363.15 K and pressures up to 63 bar. At conditions approaching infinite dilution of a gas, the Fick mutual diffusivity of the mixture measured by DLS and the self-diffusivity of the corresponding gas calculated by MD simulations match, which could be generally found within combined uncertainties. The obtained diffusivities are in agreement with literature data for the same or comparable systems as well as with the general trend of increasing diffusivities for decreasing IL viscosities. The DLS and MD results reveal distinctly larger molecular diffusivities for [EMIM][B(CN)(4)]-hydrogen mixtures compared to mixtures with all other gases. This behavior results in the failure of an empirical correlation with the molar volumes of the gases at their normal boiling points. The DLS experiments also showed that there is no noticeable influence of the dissolved gas and temperature on the thermal diffusivity of the studied systems.

Mutual and Thermal Diffusivity of Binary Mixtures of the Ionic Liquids [BMIM][C(CN)(3)] and [BMIM][B(CN)(4)] with Dissolved CO2 by Dynamic Light Scattering - Rausch, Michael Heinrich; Heller, Andreas; Herbst, Jonas; Koller, Thomas Manfred; Bahlmann, Matthias; Schulz, Peter; Wasserscheid, Peter; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2014)
Ionic liqs. (ILs) are promising solvents for gas sepn. processes such as carbon dioxide (CO2) capture from flue gases. For the design of corresponding processes and app., thermophys. properties of ILs contg. dissolved gases are required. In the present study, it is demonstrated that with a single optical setup, mutual and thermal diffusivities as well as refractive indexes can be measured quasi-simultaneously for such mixts. Dynamic light scattering (DLS) from bulk fluids was applied to det. mutual and thermal diffusivities for mixts. of 1-butyl-3-methylimidazolium tricyanomethanide ([BMIM][C(CN)3]) or 1-butyl-3-methylimidazolium tetracyanoborate ([BMIM][B(CN)4]) with dissolved CO2 at temps. from 303.15 to 333.15 K and pressures between 2 and 26 bar in macroscopic thermodn. equil. Good agreement with literature data and only slight differences between the diffusivities measured for the two systems at the same temp. and comparable mole fractions of CO2 were found. Increasing mutual diffusivities with increasing mole fractions of CO2 are consistent with decreasing viscosities reported for other IL-CO2 mixts. in the literature and can be attributed to weakening of mol. interactions by the dissolved gas. For the conditions studied, no dependence of the thermal diffusivity on the temp. or the mole fraction of CO2 could be found. [on SciFinder(R)]
Keywords: mutual thermal diffusivity binary mixt ionic liq carbon dioxide; refractive index carbon dioxide dissolved ionic liq

Simultaneous Determination of Thermal and Mutual Diffusivity of Binary Mixtures of n-Octacosane with Carbon Monoxide, Hydrogen, and Water by Dynamic Light Scattering - Heller, Andreas; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fleys, Matthieu S. H.; Bos, A. N. Rene; van der Laan, Gerard P.; Makrodimitri, Zoi A.; Economou, Ioannis G.; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2014)
It is demonstrated that thermal and mutual diffusivities of binary mixtures of n-octacosane (n-C28H58) with carbon monoxide (CO), hydrogen (H-2), and water (H2O) are simultaneously accessible by dynamic light scattering (DLS). As the light-scattering signals originating from thermal and concentration fluctuations appear in similar time scales, different data evaluation strategies were tested to achieve minimum uncertainties in the resulting transport properties. To test the agreement of the respective theoretical model with the DLS signals in the regression, an improved multifit procedure is introduced. With the selected data evaluation strategy, uncertainties of 4 to 15% and 4 to 30% in the thermal and mutual diffusivities, respectively, could be obtained for the binary mixtures. The mutual diffusivities for the mixtures measured at temperatures ranging from 398 to 523 K and pressures of 5 to 30 bar at saturation conditions are in good agreement with molecular dynamics simulations and data from the literature.

Thermal and Mutual Diffusivity of Binary Mixtures of n-Dodecane and n-Tetracontane with Carbon Monoxide, Hydrogen, and Water from Dynamic Light Scattering (DLS) - Heller, Andreas; Fleys, Matthieu S. H.; Chen, Jiaqi; van der Laan, Gerard P.; Rausch, Michael Heinrich; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2016)
The present work represents a continuation of a former study where the simultaneous determination of thermal and mutual diffusivity for binary mixtures of n-octacosane (n-C28H58) with dissolved carbon monoxide (CO), hydrogen (H-2), or water (H2O) by using dynamic light scattering (DLS) was demonstrated. Here, the same properties are studied for binary mixtures of the n-alkanes n-dodecane (n-C12H26) or n-tetracontane (n-C40H82) with dissolved CO, H-2, or H2O. In most cases, expanded relative uncertainties (k = 2) ranging from 2 to 12 % and 3 to 25 % for the thermal and mutual diffusivities could be obtained. The experimental mutual diffusivities for mixtures of n-C12H26 with CO, H-2, or H2O measured at temperatures from 398 to 524 K and pressures from 0.2 to 4.2 MPa at saturation conditions agree well with molecular dynamics (MD) simulations using atomistic models and with experimental data from literature. Binary mixtures of n-C40H82 with dissolved CO, H-2, or H2O were investigated in a temperature range from 447 to 498 K and pressures from 0.3 to 3.9 MPa. For mixtures with n-C40H82, the accessible temperature range was limited due to a change in the optical characteristics of the sample at elevated temperatures where DLS measurements suffered from absorption effects and particle scattering.

Thermophysical Properties of the Refrigerant Mixtures R417A and R417B from Dynamic Light Scattering (DLS) - Heller, Andreas; Rausch, Michael Heinrich; Flohr, Felix; Leipertz, Alfred; Fröba, Andreas Paul (International Journal of Thermophysics, 2012)
Dynamic light scattering (DLS) has been used for the measurement of several thermophysical properties of the refrigerant mixtures R417A (50% by mass 1,1,1,2-tetrafluoroethane-R134a, 46.6% pentafluoroethane-R125, 3.4% n-butane-R600) and R417B (79% by mass R125, 18.25% R134a, 2.75% R600). Both refrigerant mixtures are designed for a replacement of R22 (chlorodifluoromethane) in existing refrigeration systems. Thermal diffusivity and sound speed have been obtained by light scattering from the bulk fluid for the liquid phase under saturation conditions over a temperature range from about 283K up to the liquid-vapor critical point with estimated uncertainties between 1% and 3% and between 0.5% and 2%, respectively. By applying the method of DLS to a liquid-vapor interface, also called surface light scattering, the saturated liquid kinematic viscosity and surface tension have been determined simultaneously. These properties have been measured from 253.15K up to the liquid-vapor critical point with estimated uncertainties between 1% and 3% for kinematic viscosity and between 1% and 2% for surface tension. The measured thermal diffusivity, sound speed, kinematic viscosity, and surface tension are represented by interpolating expressions with differences between the experimental and calculated values that are comparable with but always smaller than the uncertainties. The results are discussed in detail in comparison with literature data and with various prediction methods.
Keywords: Kinematic viscosity; R22 substitute; R417A; R417B; Sound speed; Surface tension; Thermal diffusivity

Viscosity of heavy n-alkanes and diffusion of gases therein based on molecular dynamics simulations and empirical correlations - Makrodimitri, Zoi A.; Heller, Andreas; Koller, Thomas Manfred; Rausch, Michael Heinrich; Fleys, Matthieu S. H.; Bos, A. N. Rene; van der Laan, Gerard P.; Fröba, Andreas Paul; Economou, Ioannis G. (Journal of Chemical Thermodynamics, 2015)
The viscosity of pure n-alkanes and n-alkane mixtures was studied by molecular dynamics (MD) simulations using the Green-Kubo method. n-Alkane molecules were modeled based on the Transferable Potential for Phase Equilibria (TraPPE) united atom force field. MD simulations at constant number of molecules or particles, volume and temperature (NVT) were performed for n-C-8 up to n-C-96 at different temperatures as well as for binary and six-component n-alkane mixtures which are considered as prototypes for the hydrocarbon wax produced during the Gas-To-Liquid (GTL) Fischer-Tropsch process. For the pure n-alkanes, good agreement between our simulated viscosities and existing experimental data was observed. In the case of the n-alkane mixtures, the composition dependence of viscosity was examined. The simulated viscosity results were compared with literature empirical correlations. Moreover, a new macroscopic empirical correlation for the calculation of self-diffusion coefficients of hydrogen, carbon monoxide, and water in n-alkanes and mixtures of n-alkanes was developed by combining viscosity and self-diffusion coefficient values in n-alkanes. The correlation was compared with the simulation data and an average absolute deviation (AAD) of 11.3% for pure n-alkanes and 14.3% for n-alkane mixtures was obtained. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Molecular dynamics simulation; Viscosity; Diffusion coefficient; Heavy n-alkanes